2019
DOI: 10.1136/jmedgenet-2018-105834
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing and ACMG-AMP-2015-based classification of PALB2 genetic variants: an ENIGMA report

Abstract: BackgroundPALB2 monoallelic loss-of-function germ-line variants confer a breast cancer risk comparable to the average BRCA2 pathogenic variant. Recommendations for risk reduction strategies in carriers are similar. Elaborating robust criteria to identify loss-of-function variants in PALB2—without incurring overprediction—is thus of paramount clinical relevance. Towards this aim, we have performed a comprehensive characterisation of alternative splicing in PALB2, analysing its relevance for the classification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 26 publications
1
28
0
9
Order By: Relevance
“…Libraries were paired-end sequenced on an Illumina HiSeq 2000 (2x50 bp, two breast samples) or a NextSeq 500 (2x75 bp, remaining seven samples). Sequence reads were analyzed as described previously (Lopez-Perolio et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Libraries were paired-end sequenced on an Illumina HiSeq 2000 (2x50 bp, two breast samples) or a NextSeq 500 (2x75 bp, remaining seven samples). Sequence reads were analyzed as described previously (Lopez-Perolio et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Massively parallel complementary DNA sequencing (RNA-seq) has further advanced our ability to characterize and quantify gene transcripts, and will therefore become a key technology for measuring gene expression changes in clinical diagnostics. Recent studies have begun to demonstrate the utility of RNA-seq for identifying mRNA splicing events in breast cancer susceptibility genes, including BRCA1 (Davy et al, 2017; de Jong et al, 2017; Hojny et al, 2017), BRCA2 (Davy et al, 2017), PALB2 (Lopez-Perolio et al, 2019), and BARD1 (Davy et al, 2017). These studies revealed that key advantages of using RNA-seq over RT-PCR is the ability to quantitatively assess multiple splicing events across the whole transcript in one sequencing assay.…”
Section: Introductionmentioning
confidence: 99%
“…This is of course important since some splice variants can result in the expression of a transcript that may be (partially) functional. For instance, several exons in PALB2 (exons 1, 2, 4, 6, 7, 9, 10, and 11-12 combined) can be skipped due to splice site variants and still result in an in-frame transcript (Lopez-Perolio et al, 2019). Such transcripts may still express an isoform of PALB2 with an entire exon deleted, yet retain partial protein function.…”
Section: Toward the Functional Analysis Of Palb2 Vus In Rna Splicingmentioning
confidence: 99%
“…Variants and transcripts were annotated according to the Human Genome Variation Society (HGVS) guidelines on basis of the BRCA2 GenBank sequence NM000059.1. In order to simplify, we identified transcripts with a shortened code that combines the following symbols (Lopez-Perolio et al, 2019): Δ (skipping of reference exonic sequences), (inclusion of reference intronic sequences), E (exon), p (acceptor shift), q (donor shift). When necessary, the exact number of skipped or retained nucleotides is indicated.…”
Section: Methodsmentioning
confidence: 99%